Genomic characterization of Cronobacter sakazakii strains in the neonatal meningitis clonal complex 4 - Jinrui Hu; Zhenpeng Li; Yan Sun; Wenyu Shi; Xiaoli Du; Shuang Meng; Zhengfei Yu; Jinyue Liu; Stephen Forsythe; Zhigang Cui; Haijian Zhou (Food Frontiers, 2024)
Abstract Cronobacter sakazakii clonal complex 4 (CC4) is strongly associated with neonatal meningitis. However, C. sakazakii CC4‐specific pathogenicity traits have not been determined. In this study, the comparative genomic analysis of 144 genomes of C. sakazakii CC4 strains and 376 non‐CC4 C. sakazakii strains was undertaken. Twenty‐four CC4 strains were previously undescribed clinical and nonclinical strains that had been collected from various regions in China (2006–2017). The remaining genomes were of multiple sequence types of C. sakazakii strains, which had been isolated worldwide (1973–2021). The pan‐genome of C. sakazakii comprised 32,332 genes, of which 2.58% (832 genes) constituted the core genome. More C. sakazakii CC4 strains have a complete cusABCFR efflux system with a significant difference compared with non‐CC4 strains, and the ibeB‐homologous cusC gene in the cusABCFR efflux system is probably associated with the invasion of human brain microvascular endothelial cells (BMEC). In addition, the isolates with K2:CA2 capsule or type IV pili‐associated genes associated with neonatal meningitis were statistically more present in CC4 strains than non‐CC4 strains (p < .0001). The thorough description of VirB/VirD4 gene cluster for the type IV secretion system and the impB/impF and vasL/vasJ gene clusters for the type VI secretion system in C. sakazakii were provided. Overall, the specific and diverse virulence factors and genes may have led to C. sakazakii CC4 clone increasing its ability to invade human BMEC and leading to neonatal meningitis. Our findings should facilitate the development of novel strategies to prevent, diagnose, and treat C. sakazakii CC4 infections.